Lignin-Cobalt Nano-Enabled Poly(pseudo)rotaxane Supramolecular Hydrogel for Treating Chronic Wounds - Giulia Crivello; Giuliana Orlandini; Angela Gala Morena; Alessandro Torchio; Clara Mattu; Monica Boffito; Tzanko Tzanov; Gianluca Ciardelli (MDPI AG, 2023)
Chronic wounds (CWs) are a growing issue for the health care system. Their treatment requires a synergic approach to reduce both inflammation and the bacterial burden. In this work, a promising system for treating CWs was developed, comprising cobalt-lignin nanoparticles (NPs) embedded in a supramolecular (SM) hydrogel. First, NPs were obtained through cobalt reduction with phenolated lignin, and their antibacterial properties were tested against both Gram-negative and Gram-positive strains. The anti-inflammatory capacity of the NPs was proven through their ability to inhibit myeloperoxidase (MPO) and matrix metalloproteases (MMPs), which are enzymes involved in the inflammatory process and wound chronicity. Then, the NPs were loaded in an SM hydrogel based on a blend of α-cyclodextrin and custom-made poly(ether urethane)s. The nano-enabled hydrogel showed injectability, self-healing properties, and linear release of the loaded cargo. Moreover, the SM hydrogel's characteristics were optimized to absorb proteins when in contact with liquid, suggesting its capacity to uptake harmful enzymes from the wound exudate. These results render the developed multifunctional SM material an interesting candidate for the management of CWs.